The importance of strengthening the pelvic floor muscles in women's health (Research, Society and Development, 2021)
Physiotherapy in women's health has been gaining prominence in the prevention and treatment of decreased strength of the pelvic floor, which, with the weakening of the pelvic muscle, the woman can develop sexual dysfunctions, incontinence, genital prolapse and vaginal flaccidity. The purpose of this article is to demonstrate the importance of strengthening the pelvic ridge muscles to prevent dysfunctions caused by the weakening of the floor muscles. The study is a literature review of a descriptive and quantitative character, searched in databases such as Cochrane Library, Scientific Electronic Library Online (SciELO) and books with descriptors, "Sexual dysfunctions", "Pelvic Floor", "Pregnancy". Throughout their lives, women go through specific phases and periods that are determined by physical, hormonal and psychological changes, and the weakening of the pelvic floor muscles is a consequence of these changes, which may lead the woman to develop: sexual dysfunction, urinary incontinence as well as fecal, genital prolapse, sexual dissatisfaction and changes in sexual responses. It is perceived that the strengthening of the pelvic floor musculature, acts both in the prevention and in the treatment of these dysfunctions and aims to improve the muscular strength of the floor preventing dysfunctions and alterations and through the strengthening of this musculature, if there is an improvement in muscle strength, gain of pelvic mobility and increased clitoral and perineal sensitivity and increased blood flow improving the phases of sexual response, lubrication, arousal, desire and orgasm, reducing muscle tension, favoring muscle relaxation, generating body awareness and sexual quality.